Five new species of Diptilomiopidae from China (Acari: Eriophyoidea) - Xue, Xiao-Feng; Hong, X.-Y. (Zootaxa, 2005)
Five new species of diptilomipid eriophyoid mites from China are described and illustrated: Rhyncaphytoptus longipalpis sp. nov. on Bambusa sp. (Gramineae); Rhyncaphytoptus taihangensis sp. nov. on Morus alba L.(Moraceae); Rhyncaphytoptus papyriferae sp. nov. on Broussonetia papyrifera (L.) Vent. (Moraceae); Diptacus songxianensis sp. nov. on Ulmus sp.(Ulmaceae) and Trimeroptes luanchuanensis sp. nov. on Rubus sp. (Rosaceae). All species described here are vagrant on leaves.